PERFORMA PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis niloticus) PASCA PAPARAN INSEKTISIDA NABATI BERBAHAN AKTIF AZADIRACHTIN - Brainerd, Eliazer; Yustiati, Ayi; Suryana, Asep Agus Handaka; Herman, Roffi Grandiosa; Bangkit, Ibnu; Bari, Ichsan Nurul (JARI : Jurnal Akuakultur Rawa Indonesia, 2023)
Insecticides can be used to overcome pest attacks in agricultural and plantation sectors. The botanical insecticide is more widely used because more friendly to the environment than chemical insecticides. Neem is one of the plants that can be used as basic ingredient for botanical insecticides because it contains the compound azadirachtin. Insecticide enter the cultivation area because carried by flowing water. Tilapia is a fish that can be used as a bioindicator of pollution levels, water quality, and changes in the aquatic environment. This study aims to determine the effect of exposure insecticide with azadirachtin active ingredient on growth and survival rate of tilapia. This research was conducted in March and August for the preliminary test and September-October 2022 for the main test at Ciparanje Inland Aquaculture Hatchery, Padjadjaran University. The fish used in this study averaged 6,70 ± 0,014 cm. This study used experimental method, Completely Randomized Design with five treatments and three replications. The treatments used were exposure to insecticides with different doses, namely A(0 ppm), B(26.25 ppm), C(52.5 ppm), D(78.75 ppm), E(105 ppm). Parameters observed included absolute length growth and weight growth, survival rate, and water quality until 28th day. Growth and survival data analyzed using the F test and continued with Duncan's test at the 95% level of confidence. The results showed that exposure insecticide can inhibited growth and affected the survival of tilapia. Treatment C(52.5 ppm) is a safe concentration for the survival of tilapia and the highest growth is the treatment without addition of insecticide.